2019
DOI: 10.1002/stem.3026
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Stimulates PI3K/AKT and Cell Adhesion to Promote the Survival of Individualized Human Embryonic Stem Cells

Abstract: Insulin is present in most maintenance media for human embryonic stem cells (hESCs), but little is known about its essential role in the cell survival of individualized cells during passage. In this article, we show that insulin suppresses caspase cleavage and apoptosis after dissociation. Insulin activates insulin‐like growth factor (IGF) receptor and PI3K/AKT cascade to promote cell survival and its function is independent of rho‐associated protein kinase regulation. During niche reformation after passaging,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Activated IGF1R is involved in cell growth and survival and influences an array of physiological and pathological conditions . For example, IGF1R inhibition is an escape mechanism in Ewing sarcoma and IGF1R inhibitors are candidate therapies for this disease . In this study, we found that IGF1R interacts with miR‐7025‐5p and that the down‐regulation of miR‐7025‐5p increases the IGF1R mRNA levels to promote osteogenic processes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Activated IGF1R is involved in cell growth and survival and influences an array of physiological and pathological conditions . For example, IGF1R inhibition is an escape mechanism in Ewing sarcoma and IGF1R inhibitors are candidate therapies for this disease . In this study, we found that IGF1R interacts with miR‐7025‐5p and that the down‐regulation of miR‐7025‐5p increases the IGF1R mRNA levels to promote osteogenic processes.…”
Section: Discussionmentioning
confidence: 67%
“…[29][30][31] For example, IGF1R inhibition is an escape mechanism in Ewing sarcoma and IGF1R inhibitors are candidate therapies for this disease. 32 In this study, we found that IGF1R interacts with miR-7025-5p and that the down-regulation of miR-7025-5p increases the IGF1R mRNA levels to promote osteogenic processes. Moreover, we found the levels of IGF1R and miR-7025-5p remain stable during osteogenic differentiation, but the expression of the IGF1R protein increases during fracture healing, whilst the levels of miR-7025-5p decline.…”
Section: Il-10 Targets Both Innate and Adaptive Immune Responses And Ex-mentioning
confidence: 60%
“…The IGF and insulin activate the PI3K and CK2 cascades, and they are essential for hPSC maintenance (Bendall et al, 2007;Chen et al, 2011;Godoy-Parejo et al, 2019;Wang et al, 2007). This study reveals the temporal regulation of IGFs on mesodermal differentiation ( Figure S4P).…”
Section: Discussionmentioning
confidence: 67%
“…The PI3K/AKT cascade is often discussed in stem cell regulation. PI3K/AKT activation is essential to suppress caspase and cell death in hESC maintenance (Godoy-Parejo et al, 2019). During differentiation, the insulin/IGF activates the PI3K cascade to promote neuroectoderm lineage while suppressing endoderm cell fate determination (Yu and Cui, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PI (3,4,5) P3 is an intracellular second messenger in the cell that needs to transfer protein kinase B (AKT) to the membrane for activation [34]. Phosphorylated AKT mediates insulin and various growth factors to induce cell growth and promote cell survival through numerous channels [35]. ERK/MAPK is a classical signaling pathway of anti-apoptosis.…”
Section: Discussionmentioning
confidence: 99%